Influence of substrate and annealing temperatures on optical properties of RF-sputtered TiO2 thin films - Hasan, M.M. (Elsevier, 2010)
TiO2 thin films were deposited on unheated and heated glass substrates at an elevated sputtering pressure of 3 Pa by radio frequency (RF) reactive magnetron sputtering. TiO2 films deposited at room temperature were annealed in air for 1 h at various temperatures ranging from 300 to 600 °C. The structural and optical properties of the thin films were investigated using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and ultraviolet–visible–near infrared (UV–VIS–NIR) spectrophotometry. XRD results show that as-grown and post-annealed TiO2 films have anatase crystal structure. Higher substrate and annealing temperatures result in a slight increase of crystallinity. TiO2 films deposited at different substrate temperatures exhibit high visible transmittance and the transmittance decreases slightly with an increase in annealing temperature. The refractive indices (at λ = 550 nm) of the as-deposited and annealed films are found to be in the range of 2.31–2.37 and 2.31–2.35, respectively. Extinction coefficient decreases slightly with increasing substrate and annealing temperatures. The indirect and direct optical band gap of the as-grown films increases from 3.39 to 3.42 eV and 3.68 to 3.70 eV, respectively, with the increase of substrate temperatures. Annealed TiO2 films also exhibit an increase in the values of indirect and direct optical band gap.